Chemically Engineering Magnetic Anisotropy of 2D Metalloporphyrin. Issue 10 (18th July 2017) - Wang, Peng; Jiang, Xue; Hu, Jun; Zhao, Jijun
Abstract: Continuous miniaturization of magnetic units in spintronics devices inspires efforts to search for novel 2D magnetic materials with giant magnetic anisotropy energy (MAE). Through systematic first‐principles calculations, large MAE of 24 meV in W or Re embedded 2D polyporphyrin frameworks is found. Interestingly, the MAE can be enhanced up to 60 meV, through replacing the hydrogen atoms on the edges of the Re based 2D polyporphyrin framework by hydroxyl and amino radicals. Analysis of the electronic structures reveals that the enhancement of MAE is mainly attributed to charge redistributions and energy shifts of Re 5d orbitals induced by the functional radicals. The findings pave a new and feasible way for tailoring the magnetic properties of magnetic organic materials to fulfill the criteria for applications in spintronics devices at high temperature. Abstract : Chemical manipulation of small radicals of transition metal embedded 2D polyporphyrin frameworks has been proven to be an effective approach to engineer the magnetic anisotropy. By replacing the hydrogen atoms with small radical amino, the magnetic anisotropy energy is enhanced from 24 to 61 meV. This finding paves a new and feasible way to tailor the magnetic properties of magnetic organic materials.